2021
DOI: 10.1101/2021.07.19.21260726
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Genomic Surveillance Reveals Little Spread Between a Large University Campus and the Surrounding Community

Abstract: COVID-19 has had high incidence at institutions of higher education (IHE) in the United States, but the transmission dynamics in these settings are not well understood. It remains unclear to what extent IHE-associated outbreaks have contributed to transmission in nearby communities. We implemented high-density prospective genomic surveillance to investigate these dynamics at the University of Michigan-Ann Arbor and the surrounding community during the Fall 2020 semester (August 16th through November 24th). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Viral transmission among university students may also affect those in close proximity to the university. Though not the case in all large universities and surrounding communities, 5 it was found that counties with large university populations offering in-person instruction experienced a 56.2% increase in COVID-19 incidence when comparing the 21 days before and after the first day of classes in fall 2020. 6 These data suggest that viral transmission networks extend beyond universities and into surrounding communities, and may impact vulnerable community members.…”
Section: Introductionmentioning
confidence: 88%
“…Viral transmission among university students may also affect those in close proximity to the university. Though not the case in all large universities and surrounding communities, 5 it was found that counties with large university populations offering in-person instruction experienced a 56.2% increase in COVID-19 incidence when comparing the 21 days before and after the first day of classes in fall 2020. 6 These data suggest that viral transmission networks extend beyond universities and into surrounding communities, and may impact vulnerable community members.…”
Section: Introductionmentioning
confidence: 88%